(untitled) (Dhaka University Journal of Biological Sciences, 2014)
Four morphological mutants (albino, ropy, conidial band and buff) of Neurospora crassa were characterized based on morphological features and molecular markers. The mycelial color of mutants buff, ropy and conidial band were more or less orange like wild parents. Albino mutant showed colorless mycelium. The germination time of conidia of wild and other mutants ranged from 5 to 7 days while in albino it was 12 days. Esterase and acid phosphatase isozymes analysis of the N. crassa mutants clearly indicated that mutation altered the carotenoid biosynthesis pathway creating the albino mutant due to the effect UV light. Most of the mutants viz; albino, conidial band and buff showed characteristic RAPD banding profile. However, no band was found in wild EmA, Ema and mutant ropy. Highest number of RAPD bands were found in albino. The mutant albino showed very different morphological and molecular features from the rest specimens. DOI: http://dx.doi.org/10.3329/dujbs.v23i1.19831 Dhaka Univ. J. Biol. Sci. 23(1): 85-91, 2014